Cross-cultural adaptation, validation and reliability of the Medication Safety Thermometer tool for use in Brazil - Priscila Martini Bernardi Garzella; Denise Bueno; Isabela Heineck (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to perform cross-cultural adaptation, face and content validation and reliability analysis of the Medication Safety Thermometer tool for use in Brazil. Methods: the process of cross-cultural adaptation and validation followed the stages of translation, synthesis of translations, back-translation, content validation performed by experts, and face validation through pre-testing. Reliability was determined by calculating the Kappa coefficient. Results: the two translated versions were synthesized into a single version, which was back-translated and showed no divergences. The expert committee judged the adapted tool as equivalent, reaching a Content Validity Index higher than 0.8. The mean global understanding was 1.82, demonstrating face validity. The assessed items had Kappa coefficient greater than 0.61, showing agreement between observers. Conclusions: the cross-cultural adaptation of the tool was performed following an established methodology. The adapted tool showed inter-rater reliability and validity for use in Brazil.